Contributions of space syntax to research on the morphological and social history of urban space: the cases of Morella and Montblanc - Beltran Borràs, Júlia (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
The principal aim of this article is to explore the contributions of space syntax to historical research on the interactive relationship between the urban form and the social use of space. The article develops this subject and explores the spatial structure of the walled areas of Morella and Montblanc, with an emphasis on the entrance gates. The theory and methods of space syntax are applied to current urban planning and ancient plans of the two cities, and the analytical information extracted is contrasted with ethnographic observations and historical documents to provide context and solve ambiguities. The results of the analysis in Morella show that when one of the city’s entrance gates disappears the spatial culture of the place changes completely; nonetheless, the social history is inscribed in the morphological history. In the case of Montblanc, studying the evolution of the urban form provides new information on the cultural significance of the wall’s entrance gates in the city of the past. As this work concludes, space syntax is making significant contributions to research on the morphological history and the social history of urban space. These contributions may have direct consequences for design decisions in the recovery and/or management of heritage.